Analisis Kecamatan Prioritas untuk Pembangunan Sarana dan Prasarana di Kawasan Pasca Tambang Timah Kabupaten Bangka Selatan - Fahri Setiawan (P4W LPPM IPB, 2018)
Tin-mining has raised the local economy and income of South Bangka Selatan Regency, thus should have contributed to the development of infrastructure around tin-mine areas in the province. Positive impacts of tin-mining to infrastructure have not always been received by area around the tin-mine. The aim of this research is to determine priority districts for infrastructure development at post tin-mine areas in South Bangka Regency. The methods of the research were on-screen digitation, Scalogram and TOPSIS. The results of research shows that the land area of post tin-mine in South Bangka Regency covers 11,224.8 hectares, with Toboali District as the widest (5,053.3 hectares). Districts with the the most number of villages in hierarchy 1 was Toboali District (4 villages), while in hierarchy 3 was Air Gegas District (6 villages). Tin-mining has not always given positive effects to the development of regional infrastructure around tin-mine areas. Villages at Air Gegas Village and Toboali District are the priorities of infrastructure development, thus infrastructure development around tin-mining areas will be done equitable and gradually to resolve limited fund for future.